2009
DOI: 10.1016/s1001-0742(08)62421-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical incineration of dimethyl phthalate by anodic oxidation with boron-doped diamond electrode

Abstract: The anodic oxidation of aqueous solutions containing dimethyl phthalate (DMP) up to 125 mg/L with sodium sulfate (Na 2 SO 4 ) as supporting electrolyte within the pH range 2.0-10.0 was studied using a one-compartment batch reactor employing a boron-doped diamond (BDD) as anode. Electrolyses were carried out at constant current density (1.5-4.5 mA/cm 2 ). Complete mineralization was always achieved owing to the great concentration of hydroxyl radical ( . OH) generated at the BDD surface. The effects of pH, appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…1, SEM images of PbO 2 synthesized by anodic electrochemical deposition on Au/Ti/Si substrates are shown. The applied potential, deposition time and solution pH were 1.3 V, 9 minutes and ~2.0 respectively, and the concentration of source materials, HNO 3 and PbCl 2 , were 14 mM and 5 mM, respectively. Figs.…”
Section: Formation Of Pbo2 Nanostructures On Au By Anodic Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…1, SEM images of PbO 2 synthesized by anodic electrochemical deposition on Au/Ti/Si substrates are shown. The applied potential, deposition time and solution pH were 1.3 V, 9 minutes and ~2.0 respectively, and the concentration of source materials, HNO 3 and PbCl 2 , were 14 mM and 5 mM, respectively. Figs.…”
Section: Formation Of Pbo2 Nanostructures On Au By Anodic Depositionmentioning
confidence: 99%
“…4. The deposition time was 30 min, and the concentrations of source materials, HNO 3 and PbCl 2 , were 14 mM and 5mM, respectively. Different values for the applied potential were used: 1.1V for Fig.…”
Section: Pbo2 Nanostructures Formed On Ti Foil Using Anodic Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete decolorization and mineralization [16] could be realized on BDD electrode and the both progresses become slower when employing Pt or DSA electrodes as anodes. Especially, the superior features of high oxygen evolution potential and high stability endow the BDD electrode with potential widely electrochemical application in wastewater treatment.BDD electrode is regarded as the best known material for electrochemical oxidation [17][18][19], and the degradation of different pollutants has been conducted on BDD electrode including phenols, surfactants, antibiotics and medical intermediate, pesticides, pigment and dyes, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, recent study has revealed that the shortcomings of TiO 2 can be overcome by doping it with some nonmetallic elements such as N, F, S, C, B. These nonmetal elements have been proved to be beneficial doping elements in the TiO 2 through mixing their p orbital with O2p orbital to reduce the band gap energy of TiO 2 [5][6][7][8][9] . Undeniably, the modification of TiO 2 photocatalysts involves the doping with nonmetal elements resulting in a desired band-gap narrowing and an enhancement in the photocatalytic efficiency under daylight-inducing.…”
Section: Introductionmentioning
confidence: 99%